Biological training of parasitologists as making fundamentalization continuous medical education - S. Yu. Astanina (Российский паразитологический журнал)
Biological knowledge is an indispensable condition of quality of training of the parazitologists. Justification of biological knowledge system as cognitive basis of fundamental training of parazitologists is given. The complex of didactic condi- tions for implementation of this provision is defined: - the target component of educational process has to be directed on a solution of the problem of boundaries - disciplinary integration as necessary condition of improvement of quality of training of the doctors; - selection and structuring a training material of biological disciplines have to be carried out from positions of system and integrative approach; - allocation of backbone generalized didactic units «System biological know- ledge» as multifunctional integrative complexes